CRYSTAL STRUCTURE OF PUSHCHAROVSKITE - Pushcharovsky D.Yu.; Zubkova N.V.; Teat S.J.; Zaitsev V.N.; Sarp H. (My University, 2000)
Pushcharovskite, K0.02Cu1.125As0.94O5.515H4.06 (ideally CuAsO3(OH)·1.5H2O), M = 235.02, is triclinic, with space group P1, a = 13.6164(7), b = 15.6672(8), c = 19.1869(9) Å, α = 106.933(2), β = 91.531(2), γ = 98.401(2)°, V = 3863.3(3) Å3, Z = 32, ρ(o) = 3.35, ρ(c) = 3.235 g/cm3, μ = 11.40 mm-1. The crystal structure of pushcharovskite was solved and refined against data collected at the Daresbury Synchrotron Radiation Facility, using a 60 x 20 x 5 μm3 single crystal, λ = 0.6883 Å, F(000) = 3590, R 0.054 for 8343 reflections with I > 2σ(I). Pushcharovskite is a mineral characterized by some structural disorder and by the following general formula: K0.6Cu18[AsO2.8(OH)1.2]15(OH)9.6·18.6(H2O); the corresponding structural formula is K0.6Cu18[AsO2(OH)2]4 [AsO3(OH)]10[AsO4](OH)9.6·18.6(H2O). The structure contains heteropolyhedral sheets (110) formed by Cu,O polyhedra (square bipyramids and square pyramids) and by As,O,OH tetrahedra. The sheets are linked by hydrogen bonding involving the water molecules of the Cu square bipyramids and pyramids, the OH groups of the As,O,OH tetrahedra and H2O molecules localized in the interlayers. A small amount of distorted K octahedra with partial occupancy reinforce these contacts. Some vacancies in the positions of Cu atoms were revealed. The mineral is structurally related to geminite, Cu(AsO3OH)·H2O, yvonite, Cu(AsO3OH)·2H2O and fluckite, CaMn(AsO3OH)2·2H2O.